Contraceptive Practice of Married Women: Experience from a Rural Community of Bangladesh (Journal of Medicine, 2014)
Background: Bangladesh is a country having high density of population in the world. Its fertility rate ranges from 4.1 to 5.49. This study was conducted to investigate socio-demographic characteristics, type of used contraceptive method, reasons for non use of contraceptive methods and also the side effects due to use of contraceptive method among the married women in some villages of Keranigonj Upazila, Dhaka. Material and Methods: This descriptive cross sectional survey was carried out among 240 married women of reproductive age from July to December, 2012 in some villages of Keranigonj, Upazila, Dhaka. Results: The mean age of the study population was 29±6.5 years with the mean age at marriage of 17.18±2.7 years. 73(31%) were practicing some methods of contraception, while 167 (69%) were not using it. OCP (Oral Contraceptive Pill) was the commonest method of contraception followed by Condoms 12(5%), Injectable 12(5%), Implant 12(5%) & Tubectomy 6(3%). None was found using IUCD and Traditional method ( withdrawal, rhythm method ) and emergency contraceptive method. The use of contraceptives were more common in grand multipara (p35 years old ladies (p